LIMBAH FLEXY BANNER SEBAGAI IKATAN DAN ELEMEN ESTETIK PADA FURNITURE ROTAN - Sumitro, Handy Octoriawan S. (Jurnal Dimensi Seni Rupa dan Desain, 2023)
Visual waste has become a scourge in urban areas because of the massive promotion using flexy banners as the print media. Flexy banners are made from polyvinyl chloride (PVC) which is a derivative of plastic material that is difficult to break down into a serious pile of waste if ignored. Flexy banner waste can turn into a product that has functional and aesthetic values. Utilization of flexy banner waste as a bond and aesthetic element in rattan furniture is the focus of this research. This research uses the design thinking method and the ATUMICS theoretical approach as a reference for modernizing a traditional work. Perform tensile testing on the flexy banner (China), to determine the degree of elongation. Flexy banner material can be folded 2 to 4 times, to minimized the elongation. The touch of a flexy banner as a knot and a aesthetic element on rattan furniture transforms products from classic styles into contemporary ones.Keywords: banner, rattan, product, furniture